Penerapan Senam Anti Stroke pada Penderita Hipertensi di Desa Kaliputih Kecamatan Purwojati - Asri Nur Rahmawati; Madyo Maryoto; Adiratna Sekar Siwi (Journal of Community Service and Engagement, 2026)
Hypertension, or high blood pressure, is a medical condition that increases the risk of heart disease, stroke, and kidney failure. The prevalence of hypertension in Central Java in 2023 reached 31.4%, which is also estimated to apply to Banyumas. Anti-stroke exercises are one of the preventive measures because they can lower blood pressure, control cholesterol levels, and improve minor disorders in the body. The purpose of this Community Service (PkM) activity is to increase the knowledge and skills of the elderly regarding anti-stroke exercises. The PkM implementation methods included lectures, discussions, as well as pre-tests and post-tests participated in by 19 elderly people. The pre-test results showed that 84% of participants were in the low category and 16% in the sufficient category, while the post-test showed that 89% were in the high category and 11% in the sufficient category. These results indicate an increase in the elderly's knowledge about hypertension and anti-stroke exercises after the activity. The output of the PkM is the publication of an article in an accredited national journal, which is expected to be a reference for education and prevention efforts for hypertension in the elderly..